Share The Formula You Found

+Label +Description

Recently Referred Formulae

\sum_{n\neq a} p_n\frac{p_a}{1-p_n}=p_b\frac{p_a}{1-p_b}+p_c\frac{p_a}{1-p_c}+p_d\frac{p_a}{1-p_d}+p_e\frac{p_e}{1-p_n}
\sum_{n\neq a} p_n\frac{p_a}{1-p_n}=p_b\frac{p_a}{1-p_b}+p_c\frac{p_a}{1-p_c}+p_d\frac{p_a}{1-p_d}+p_\frac{p_e}{1-p_n}
\sum_{n\neq a} p_n\frac{p_a}{1-p_n}=p_b\frac{p_a}{1-p_b}+p_c\frac{p_a}{1-p_c}+p_d\frac{p_a}{1-p_d}+p_n\frac{p_e}{1-p_n}
\sum_{n\neq a} p_n\frac{p_a}{1-p_n}=p_b\frac{p_a}{1-p_b}+p_c\frac{p_a}{1-p_c}+p_d\frac{p_a}{1-p_n}+p_n\frac{p_e}{1-p_n}
\sum_{n\neq a} p_n\frac{p_a}{1-p_n}=p_b\frac{p_a}{1-p_b}+p_c\frac{p_a}{1-p_c}+p_d\frac{p_d}{1-p_n}+p_n\frac{p_e}{1-p_n}